Genetic Analysis and Complete Primary Structure of Microcin L - Pons, Anne-Marie (American Society for Microbiology, 2004)
Escherichia coli LR05, in addition to producing MccB17, J25, and D93, secretes microcin L, a newly discovered microcin that exhibits strong antibacterial activity against related Enterobacteriaceae, including Salmonella enterica serovars Typhimurium and Enteritidis. Microcin L was purified using a two-step procedure including solid-phase extraction and reverse-phase C(18) high-performance liquid chromatography. A 4,901-bp region of the DNA plasmid of E. coli LR05 was sequenced revealing that the microcin L cluster consists of four genes, mclC, mclI, mclA, and mclB. The structural gene mclC encoded a 105-amino-acid precursor with a 15-amino-acid N-terminal extension ending with a Gly-Ala motif upstream of the cleavage site. This motif is typical of the class II microcins and other gram-positive bacteriocins exported by ABC transporters. The mclI immunity gene was identified upstream of the mclC gene and encodes a 51-amino-acid protein with two potential transmembrane domains. Located on the reverse strand, two genes, mclA and mclB, encoded the proteins MclA and MclB, respectively. They bear strong relatedness with the ABC transporter proteins and accessory factors involved in the secretion of microcins H47, V, E492, and 24. The microcin L genetic system resembles the genetic organization of MccV. Furthermore the MccL primary structure has been determined. It is a 90-amino-acid peptide of 8,884 Da with two disulfide bridges. The N-terminal region has significant homologies with several gram-positive bacteriocins. The C-terminal 32-amino-acid sequence is 87.5% identical to that of MccV. Together, these results strongly indicate that microcin L is a gram-negative class II microcin.